THE ROLE OF SCHOOL ADMINISTRATORS AFFECTING THE PROFESSIONAL COMMUNITY AT SCHOOLS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE PHRA NAKRON SI AYUTTHAYA - Mougim, Wannapa; Wongsakul, Supawadee; Jarungnanthakal, Skowrat (Journal of Educational Review Faculty of Education in MCU, 2022)
This research article is for 1) study roles of school administrators working under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya, 2) study the conditions of PLC implemented at schools under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya, and 3) to analyze the role of school administrator affecting the professional community at schools under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya. A sample group consisted of 315 administrators and teachers working at the secondary schools under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya. The data were analyzed using Frequency, Percentage, Mean, Standard Deviation, and Multiple Regression Coefficient. Findings revealed that 1) the roles of school administrators working at secondary schools under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya were found in a high level, 2) overall conditions of the PLC implementation at the secondary schools under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya were found in a high level, 3) the roles of school administrators working at the secondary schools under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya on PLC implementation were found in 4 aspects. The highest effect showed on consultation, followed by facilitation support, and expectants, respectively. They affected the PLC implementation at a statistically significant level of .05.